EFFECT OF DISINFECTANTS ON THE COLOUR STABILITY OF HEAT CURE ACRYLIC RESIN - Amin, Faiza; Iqbal, Shumaila; Azizuddin, Syed (Journal of Ayub Medical College Abbottabad, 2014)
Kingdom of Saudi Arabia Background: Contaminated dentures need to be disinfected as a part of denture hygiene regimen. This study was conducted to determine the colour stability of heat cure acrylic resin after treatment with two disinfectants. Methods: This in-vitro experimental study was conducted at Dr Ishrat-ul-Ebad Khan Institute of Oral Health Sciences, Dow University of Health Sciences and Al Karam Textiles Karachi, from January to April 2012. Total 72 rectangular shaped specimens; 18 specimens were measured at baseline (control group) of the study (0 day), 18 specimens were immersed in distilled water. Eighteen (18) specimens were placed in 1% Sodium Hypochlorite solution for 20 minutes and eighteen (18) specimens were placed in Alkaline Gluteraldehyde for 10 minutes. All specimens were polished, stored in distilled water for 24 hours prior to experiment. All the specimens were immersed twice daily for total of 60 days. After 60 days of immersion the specimens were tested for colour changes with spectrophotometer. SPSS-16 was used for statistical analysis. Results: There was statistically significant difference in the colour change (Î”E) between all groups (p<0.001) after 60 days of immersion. At baseline (0 day), trace amount of colour change was observed whereas when specimens immersed in distilled water undergo slight change in colour after 60 days of immersion. Furthermore, specimens immersed in 1% Sodium hypochlorite for 20 minutes and 2%AlkalineGluteraldehyde for 10 minutes for 60 days twice a day showed noticeable changes in colour. Conclusion: There results of the study advocated that the colour stability of denture base acrylic resin is affected by the disinfectants used. Keywords: Heat cure acrylic resin. Colour stability. Spectro photometer. Disinfectants